2020
DOI: 10.1371/journal.pone.0228474
|View full text |Cite
|
Sign up to set email alerts
|

Recovery in cognitive motor dissociation after severe brain injury: A cohort study

Abstract: Objective To investigate the functional and cognitive outcomes during early intensive neurorehabilitation and to compare the recovery patterns of patients presenting with cognitive motor dissociation (CMD), disorders of consciousness (DOC) and non-DOC. Methods We conducted a single center observational cohort study of 141 patients with severe acquired brain injury, consecutively admitted to an acute neurorehabilitation unit. We divided patients into three groups according to initial neurobehavioral diagnosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 47 publications
(55 reference statements)
1
38
1
1
Order By: Relevance
“…Imaging (MRI or CT)-dominant sided parietalfronto-temporal lesions clinical CMD from those with true DOC [7,8,28]. The MBT was reported to detect residual cognition at very early stages after brain injury [7,8] and the present study showed consistent findings despite the presence of pitfalls.…”
Section: Discussionsupporting
confidence: 73%
“…Imaging (MRI or CT)-dominant sided parietalfronto-temporal lesions clinical CMD from those with true DOC [7,8,28]. The MBT was reported to detect residual cognition at very early stages after brain injury [7,8] and the present study showed consistent findings despite the presence of pitfalls.…”
Section: Discussionsupporting
confidence: 73%
“…A new behavioural assessment tool, the Motor Behaviour Tool — Revised (MBT‐r) 202 , has also been developed to complement the CRS-R by identifying subtle motor behaviours that reveal residual cognition. Evidence from a sample of 141 patients receiving inpatient rehabilitative care for severe brain injuries suggests that the MBT-r used in conjunction with the CRS-R detects consciousness with a greater sensitivity than the CRS-R alone 203 . Moreover, behavioural diagnoses derived from the MBT-r predicted functional recovery at discharge from the inpatient rehabilitation centre 203 .…”
Section: Subacute-to-chronic Docmentioning
confidence: 99%
“…These patients are referred to as patients with cognitive motor dissociation (CMD; Schiff, 2015 ). With the current assessment tools, patients with CMD are easily confused with patients with UWS or in MCS− ( Schiff, 2015 ; Edlow et al , 2017 ), however; it is crucial to be able to differentiate the groups, as patients with CMD are likely to have better functional outcomes ( Jöhr et al , 2020 ). Whether to regard CMD as a clinical dimension within DoC or as a patient category of its own is still a matter of some debate ( Schiff, 2015 ; Noel et al , 2019 ; Pincherle et al , 2019 ; Jöhr et al , 2020 ), but the importance of being able to recognize patients with CMD is undisputed.…”
mentioning
confidence: 99%
“…With the current assessment tools, patients with CMD are easily confused with patients with UWS or in MCS− ( Schiff, 2015 ; Edlow et al , 2017 ), however; it is crucial to be able to differentiate the groups, as patients with CMD are likely to have better functional outcomes ( Jöhr et al , 2020 ). Whether to regard CMD as a clinical dimension within DoC or as a patient category of its own is still a matter of some debate ( Schiff, 2015 ; Noel et al , 2019 ; Pincherle et al , 2019 ; Jöhr et al , 2020 ), but the importance of being able to recognize patients with CMD is undisputed. The revised Motor Behaviour Tool has been suggested to help detect even very subtle signs of motor behaviour and thereby better differentiate patients with CMD from other patient categories ( Pignat et al , 2016 ; Pincherle et al , 2019 ).…”
mentioning
confidence: 99%